Personality in history: modern approaches - Yedgina, G.T.; Abou Taam, Kh.; Uskembayev, K.S. (Ye.A.Buketov Karaganda State University Publish hous, 2018)
The article examines the problem of the role of the individual in history that always remains relevant for each generation. The authors cite the factors and reasons that determine the degree of influence of historical figures on society, make an analysis of modern views on the role of the individual in history. The work of Sydney Hook «Hero in History. Investigation of limits and possibilities» (synergistic studies) is considered. The socalled counterfactual (or alternative) history that explores the hypothetical alternatives under non-existent scenarios is developing quite actively, especially in recent decades. An analysis of the state of the problem of the role of the individual in history shows that it is far from its final decision, that this level of its research is absolutely insufficient and needs to be deepened and systematized, as well as in need of new ideas. The article also examines the role of individual actors in the process of the formation of states and their evolution. The authors conclude that a person put forward at the level of the head of state is responsible for the life and development of this society. But not everything depends on the head. The society that elected him also plays a huge role in the development of the state.
Тарихтағы тұлға: заманауи тəсілдер
Личность в истории: современные подходы
Keywords: personality; history; historical; role of personality; role in history; hero; individual